Designing an international research experience for graduate students - Schneider, Verena; Grau, David; Ariaratnam, Samuel T. (Frontiers in Education, 2023)
As a result of the ongoing globalization, international student experiences are becoming fundamental to advance students’ development and knowledge. Even though such growing importance, the body of knowledge regarding international interventions is dominated by subjective accounts and lacks contrasted results. In order to design an international research experience for graduate students, recommendations on the design and content of such experiences based on the review of literature were explored. A qualitative and bibliographical analysis of 40 studies evaluating the influence of international student interventions informed about the variables that such interventions should measure and the impact of such experiences on student development. Researchers especially measured the competencies intercultural development (83%), intellectual growth (58%), personal development (58%), professional development (50%), and academic development (15%). However, most of the studies failed to develop an appropriate research design that enables researchers to capture the breadth and depth of an international intervention. Results include addressing various competencies that students can gain during their experience abroad, using mixed methods to collect the data, whereby data should be collected at different time points including before, and multiple times after the international experience by different means.